2019
DOI: 10.2147/idr.s192540
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiology of carbapenem-resistant Enterobacteriaceae: a 5-year experience at a tertiary care hospital</p>

Abstract: Purpose The incidence of carbapenem-resistant Enterobacteriaceae (CRE) has been increasing worldwide. Ertapenem resistance is mediated by non-carbapenemase mechanisms, and has less of an effect on susceptibility to imipenem and meropenem. This study aimed to study the epidemiology of CRE, and to compare risk factors and related mortality between non-susceptibility to ertapenem alone Enterobacteriaceae (NSEE), with non-susceptibility to other carbapenems (imipenem, meropenem, or doripenem) Enteroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 25 publications
1
33
1
Order By: Relevance
“…The prevalence of CRE among inpatients 11.11% (17/153) was more when compared to that among outpatients 3.27% (5/153) in the hospital. This also shows that CRE can be both hospital and community acquired and that the transmission of CRE infection is more likely in hospitals [20][21][22].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The prevalence of CRE among inpatients 11.11% (17/153) was more when compared to that among outpatients 3.27% (5/153) in the hospital. This also shows that CRE can be both hospital and community acquired and that the transmission of CRE infection is more likely in hospitals [20][21][22].…”
Section: Discussionmentioning
confidence: 71%
“…While our study showed that of the factors investigated, only literacy levels (p value = 0.0058) and hospitalization (p value < 0.0001) actually affected the rate of CRE infections; the infection rates of enterobacteriaceae generally were found to be affected by factors such as age, marital status, level of education and hospital setting. Other studies proved that younger age group and hospitalization are common risk factors for Gram-negative enterobacteriaceae (GNE) infections [18,19] while hospitalization remains the leading cause of CRE infections [20][21][22]. Since hospitalization is a strong risk factor in CRE colonization; clinicians, other health workers and in fact, everyone should join hands to reduce patients' length of stay in hospitals as this will reduce the risk of spread of CRE as well as control them.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a paucity of data for evaluating the impact of individual antibiotics on the intestinal microbiota [ 38 , 39 ], a recent publication showed that carbapenem use was independently predictive of high relative abundance of KPC-producing K. pneumoniae in the gut microbiota [ 40 ]. Interestingly, one epidemiologic study revealed that the incidence of CRE may rise with increased hospital-wide carbapenem use over time [ 41 ]. From our point of view, a multifaceted infection control program for CPE should include targeted carbapenem stewardship that has already been used in the control of CPE outbreaks [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] CRKPs are often extremely drug resistant to most available antimicrobial agents and associated with high morbidity and mortality, as well as high cost. 10 Thus, appropriate measures to control their infections are in urgent need.…”
Section: Introductionmentioning
confidence: 99%